Assessment of the antibacterial activity of macroalgae Cladophora crispata extract against extended spectrum beta-lactamase producing Escherichia coli isolated from diarrheic children - Uday Abdul-Reda Hussein (University of Thi-Qar Journal of Science, 2019)
Background:  Diarrhea is a major cause of morbidity and mortality in children under 5 years old in developing countries. Objective: This study designed to investigate the occurrence of extended spectrum beta-lactamase producing Escherichia coli  (E. coli ) as etiological infectious agents of  diarrhea in children, assessment of their susceptibility/resistance to antibiotics, and to evaluate  the antibacterial activity of the macroalgae Cladophora crispata extract towards these bacteria . Materials and Methods: 150 diarrheic stool samples were collected from children less than 5 years and cultured. The isolated bacteria were subjected to various identification and biochemical tests. Then all the  isolated bacteria (E. coli ) were subjected to ESBL-producing screening by double-disc synergy test, the antibacterial activity of algal extract and antibiotic susceptibility test against  tested bacteria  were determined by using agar well diffusion  and disc diffusion methods respectively . Results: Out of total 150 samples, only 18 isolates revealed the presence of extended spectrum β-lactamase producing E. coli, which showed highly susceptibility to gentamicin and amikacin, Cladophora crispata extract revealed a strong antibacterial activity against ESBL-producing E. coli. Conclusion: Cladophora crispata extract showed a strong antibacterial activity against ESBL-producing E. coli which can be exploited as source of antibacterial drugs to control and treatment diarrheal infection caused by these bacteria.